=0\\ \frac{(-x^2+x+6)(2x^2+3x-5) }{(x-4)(x-1)}>=0\\ \frac{(-x^2+x+6)(x^2+1,5x-2,5) }{(x-4)(x-1)}>=0\\ \frac{-(x^2-x-6)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\ \frac{-(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\ " alt="\frac{(-6x^2+6x+36)(2x^2+3x-5) }{(x-4)(x-1)}>=0\\ \frac{(-x^2+x+6)(2x^2+3x-5) }{(x-4)(x-1)}>=0\\ \frac{(-x^2+x+6)(x^2+1,5x-2,5) }{(x-4)(x-1)}>=0\\ \frac{-(x^2-x-6)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\ \frac{-(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}>=0\\ " align="absmiddle" class="latex-formula">
Обе части на -1:
![\frac{(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}<=0\\\begin{cases} x=3\\x=-2\\x=-2.5\\ x=1\\x\neq 1\\x \neq4 \end{cases} \frac{(x-3)(x+2)(x+2,5)(x-1) }{(x-4)(x-1)}<=0\\\begin{cases} x=3\\x=-2\\x=-2.5\\ x=1\\x\neq 1\\x \neq4 \end{cases}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-3%29%28x%2B2%29%28x%2B2%2C5%29%28x-1%29+%7D%7B%28x-4%29%28x-1%29%7D%3C%3D0%5C%5C%5Cbegin%7Bcases%7D+x%3D3%5C%5Cx%3D-2%5C%5Cx%3D-2.5%5C%5C+x%3D1%5C%5Cx%5Cneq+1%5C%5Cx+%5Cneq4+%5Cend%7Bcases%7D+)
Во всех точках ф-ия будет менять знак, за искл. x=1
-2,5 -2 1 3 4
--------\----------\-------------\----------\------------\----------x
+ - + + - +
Ответ [-2,5;-2] [3;4)